The Role of Lifestyle in Mediating the Influence of Financial Literacy and Income on the Decision to Use Paylater among Gen Z - Nanda Putri; Hedwigis Esti Riwayati (Dinasti International Journal of Digital Business Management, 2026)
This study aims to examine the influence of financial literacy and income on paylater usage decisions in Gen Z, as well as to examine the role of lifestyle as a mediating variable in this relationship. This study was conducted on Gen Z employees at the Victoria Financial Group using a quantitative approach with a survey method involving 119 respondents. Data analysis was conducted using Structural Equation Modeling–Partial Least Square to test the direct and mediating relationships between variables. The results show that financial literacy and income have a positive but insignificant effect on paylater usage decisions. Meanwhile, lifestyle has a significant positive effect on paylater usage decisions among Gen Z. Financial literacy significantly influences lifestyle. However, income does not influence lifestyle. This study shows that lifestyle is able to mediate the relationship between financial literacy and paylater usage decisions, however, lifestyle is unable to mediate the relationship between income and paylater usage decisions. These results emphasize the importance of financial literacy and income in influencing paylater usage decisions, with lifestyle acting as a significant mediator of financial literacy.